3 UMPSA start-up companies ready to penetrate globally competitive technology markets - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 12 October 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues its proactive efforts in the commercialisation of university research outputs through the Technology Licensing Agreement Document Exchange Ceremony with three university start-up companies, namely MNR Multitech Sdn. Bhd., Edgify Solutions Sdn. Bhd., and TML Lab Sdn. Bhd.